MEDIA ALTERNATIF KACANG TANAH UNTUK PERTUMBUHAN BAKTERI - Mily Zamilah; Undang Ruhimat; Doni Setiawan (Journal of Indonesian Medical Laboratory and Science, 2020)
The high cost of instant media such as nutrient agar encourages researchers to find alternative media from raw materials that are readily available and cheap. The composition of the media, which is very important for the growth of bacteria, one of which is protein. The content can be obtained from nuts, one of which is groundnut (Arachis hypogaea L). This study aims to determine the growth of Staphylococcus aureus and Escherichia coli bacteria on peanut media which are used as alternative media for Nutrient Agar (NA) substitution. The research method used is Total Plate Count. Escherichia coli bacterial colonies that grew on peanut media were 43 CFU, and colonies that grew on NA media were 238 CFU. While the growth of Staphylococcus aureus bacterial colonies in peanut media was 32 CFU and bacterial colonies growing on NA media were 217 CFU. The conclusion is that peanut media can be used as an alternative media with the growth of Escherichia coli and Staphylococcus aureus bacteria that are in accordance with Standard Plate Count.